The use of visual aids as feedback and its impact on the level of performance of some basic - HudaNajiZaidan,; Walhan Hameed, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The use of advanced modern devices and tools as far as the way of thinking means to develop an educational system, that is, followers of the curriculum, style and method of work, proceed in a clearly defined sequence in which all the capabilities offered by technology are used according to the theories of learning and education to achieve the goals of the educational system. Also, this system works to create an educational environment in which the learner has his educational experience by learning how to use all sources of knowledge and assistive technology means in order to reach the information himself. basic hand reel:1. In light of the conclusions, the researchers recommend the following2. Using visual aids as an aid in learning other skills.The use of still images in order for students to obtain information in order to reinforce lessons and other activities